THEORETICAL SUBSTANTIATION OF THE CONCEPT OF SPEECH ERRORS IN PSYCHOLINGUISTICS (Academia Science Repository, 2023)
In the course of a psycholinguistic study, the causes of speech disorders in younger schoolchildren are identified. Speech disorders of children with mental retardation are investigated. The causes of speech disorders in younger schoolchildren with normal and mental retardation are systematized, the difference in the levels of speech ontogenesis is determined.